2012
DOI: 10.12989/ose.2012.2.1.069
|View full text |Cite
|
Sign up to set email alerts
|

Reducing hydroelastic response of very large floating structures by altering their plan shapes

Abstract: Presented herein is a study on reducing the hydroelastic response of very large floating structures (VLFS) by altering their plan shapes. Two different categories of VLFS geometries are considered. The first category comprises longish VLFSs with different fore/aft end shapes but keeping their aspect ratios constant. The second category comprises various polygonal VLFS plan shapes that are confined within a square boundary or a circle. For the hydroelastic analysis, the water is modeled as an ideal fluid and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This suggests that placing a floating breakwater [48,49] at the windward side of the layout might be effective in mitigating the hydroelastic response of the OFPV. Alternatively, the OFPV platform located at the windward side of the layout may be stiffened up such as by using material with a higher Young's modulus E or using modular units with greater depth h. Other means such as altering the layout configuration of the OFPV [50] or using an articulated plate anti-motion device [51,52] could be adopted to mitigate the hydroelastic response of the OFPV. It is also interesting to note that the χ values for OFPV-I are still lower compared to their separated counterparts considered in OFPV-II.…”
Section: Ofpv-iimentioning
confidence: 99%
“…This suggests that placing a floating breakwater [48,49] at the windward side of the layout might be effective in mitigating the hydroelastic response of the OFPV. Alternatively, the OFPV platform located at the windward side of the layout may be stiffened up such as by using material with a higher Young's modulus E or using modular units with greater depth h. Other means such as altering the layout configuration of the OFPV [50] or using an articulated plate anti-motion device [51,52] could be adopted to mitigate the hydroelastic response of the OFPV. It is also interesting to note that the χ values for OFPV-I are still lower compared to their separated counterparts considered in OFPV-II.…”
Section: Ofpv-iimentioning
confidence: 99%
“…The use of air cushions for support is another innovative approach to reduce the wave-induced moments and structural loads of a VLFS, and the magnitude of the reduction is determined by the size of the air cushion [19,20]. Tay and Wang [21] investigated two different VLFS geometries in head seas and found that the hydroelastic response could be significantly reduced by modifying the plan shape. An innovative solution has been proposed and found to be effective for reducing the hydroelastic response and stress resultants of a pontoon-type VLFS, by positioning the flexible line connectors suitably and utilizing gill cells appropriately [22,23].…”
Section: Introductionmentioning
confidence: 99%